2022
DOI: 10.1080/21645515.2022.2047582
|View full text |Cite
|
Sign up to set email alerts
|

A serological investigation in Southern Italy: was SARS-CoV-2 circulating in late 2019?

Abstract: In March 2020, the first pandemic caused by a coronavirus was declared by the World Health Organization. Italy was one of the first and most severely affected countries, particularly the northern part of the country. The latest evidence suggests that the virus could have been circulating, at least in Italy, before the first autochthonous SARS-COV-2 case was detected in February 2020. The present study aimed to investigate the presence of antibodies against SARS-CoV-2 in human serum samples collected in the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 50 publications
2
7
0
Order By: Relevance
“…The first positive sample for IgG as well as for IgG RBD and a neutralizing antibody was collected on 2 March 2020, 4 days after the first case of infection was detected in Siena (27 February) and 7 days before the national lockdown was implemented on 9 March. Considering that the median time to develop IgG antibodies has been estimated to be 14 days [ 15 ] after exposure, our results suggest that SARS-CoV-2 was circulating in the area well before the first case was ascertained, as reported from other studies [ 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 79%
“…The first positive sample for IgG as well as for IgG RBD and a neutralizing antibody was collected on 2 March 2020, 4 days after the first case of infection was detected in Siena (27 February) and 7 days before the national lockdown was implemented on 9 March. Considering that the median time to develop IgG antibodies has been estimated to be 14 days [ 15 ] after exposure, our results suggest that SARS-CoV-2 was circulating in the area well before the first case was ascertained, as reported from other studies [ 16 , 17 , 18 ].…”
Section: Discussionsupporting
confidence: 79%
“…Investigations of Montomoli et al (2021) in Lombardy suggest the presence of SARS-CoV-2 antibodies in some samples collected in the prepandemic period. Similar serological investigations in Southern Italy in Apulia region (Trombetta et al, 2022) suggest that the virus had been circulating from October 2019, before the first case was detected. Cereda et al (2021) also confirmed that epidemic started much earlier in Italy than February 20, 2020.…”
Section: Introductionsupporting
confidence: 57%
“…A ten-fold increase in the proportion of samples positive for infection-induced antibodies was found between the two serosurveys, and a twenty-fold increase in seroprevalence was estimated. It is beyond the remit of the current study to investigate the role of these potential early cases in determining the subsequent spread of COVID-19 in our region, however these findings could fit with the hypothesis that a less transmissible progenitor of the virus was silently circulating prior to the identification of the first official cases (Trombetta et al, 2022). Growing evidence suggests that multiple sporadic introductions of SARS-CoV-2 occurred initially in Italy, which did not lead to sustained transmission, until the introduction of the D614G mutant in North-Western Italy in February 2020 (Lai et al, 2022).…”
Section: Discussionmentioning
confidence: 62%
“…This finding suggests SARS-CoV-2 circulation in Piedmont pre-dating the first officially reported cases in Piedmont (February 2020), Italy (January 2020), and even the first identification in Wuhan, China (December 2019) (Pubblicazione, 2021). Several Italian and international studies have identified possible COVID-19 cases prior to these dates (Deslandes et al, 2020;Apolone et al, 2021;Gragnani et al, 2021;Trombetta et al, 2022), and a recent study has suggested COVID-19 could have originated in late summer 2019, based on significant changes in hospital traffic and search engine data in Wuhan (Nsoesie et al, 2020). Notably, Apolone et al identified reactivity to RBD among two samples collected in Piedmont at the end of September 2019, and 10 out of the 111 possible COVID-19 cases identified throughout the entire study period (September 2019 -March 2020) where residents of Piedmont (Apolone et al, 2021).…”
Section: Discussionmentioning
confidence: 99%